Reassessing the value of university lectures. Issue 6 (18th August 2017) - French, Sarah; Kennedy, Gregor
ABSTRACT: This paper discusses the role of the lecture in contemporary higher education. Moving beyond the polarised perspectives that characterise recent debates on the subject, it considers both the potential problems and possible pedagogical, practical and social benefits of the lecture as a mode of teaching and learning. Through an examination of scholarly literature on the pedagogical uses of the lecture as well as recent articles on its place in the future of higher education, we outline the key arguments and highlight some of the problems, contradictions and inconsistencies implicit in the debates. Drawing upon the recurring themes in the literature, we identify seven reasons as to why the lecture continues to be valuable in contemporary higher education. However, we also suggest that more innovative approaches to lecturing as well as alternatives to lectures are needed to adapt to a changing educational environment.